Improved design solution for motion resistance problem through integration of robust design and theory of inventive principle (TRIZ) - Alias, Arman (2015)
Solving design problem related to technical contradiction are very challenging for engineers. There are always design constraints which require engineers to compromise certain specification and requirement. Trying to solve design problems traditionally is difficult and often leads to trial-and-errors. This research is a study of systematic problem solving approach related to technical contradiction through combination of robust design method and TRIZ methodology to generate concept solutions. Using a case study of vacuum cleaner motion resistance issue, five solutions options are identified and tested to verify the improvement ideas. The result shows that the integration of TRIZ into robust design method at problem formulation stage has created a more capable problem solving definition and solution generation scheme. The motion resistance is reduced significantly to more than half, which is from 76.47N to 26.48N. The pick-up performance is slightly dropped by 5% compare to the original design. However, this 5% drop is considerably minimal when compare to significant improvement on motion resistance.